The Wandering Lake - Hedin, Sven (London George Routledge & Sons, Ltd., 1940)
The lake of Lop-nor, the 'heart of the heart of Asia', is one of the world's strangest phenomena. Today, this once great lake - a mighty reservoir in the desert - is nothing but windblown sand and salty marsh. This title presents an account of a now-vanished world.
Include Sketches, Illustrations, Maps and Index.
With 32 Illustrations, 76 Sketches and 10 Maps
Keywords: China--Lop Nur -- Travel -- China--Xinjiang Uygur Zizhiqu -- Hedin, Sven Anders, 1865-1952 -- China -- Lakes